Oscillatory motor network activity during rest and movement: an fNIRS study - Bajaj, Sahil; Drake, Daniel; Butler, Andrew J.; Dhamala, Mukesh (Frontiers in Systems Neuroscience, 2014)
Coherent network oscillations (< 0.1 Hz) linking distributed brain regions are commonly observed in the brain during both rest and task conditions. What oscillatory network exists and how network oscillations change in connectivity strength, frequency and direction when going from rest to explicit task are topics of recent inquiry. Here, we study network oscillations within the sensorimotor regions of able-bodied individuals using hemodynamic activity as measured by functional near-infrared spectroscopy (fNIRS). Using spectral interdependency methods, we examined how the supplementary motor area (SMA), the left premotor cortex (LPMC) and the left primary motor cortex (LM1) are bound as a network during extended resting state (RS) and between-tasks resting state (btRS), and how the activity of the network changes as participants execute left, right and bilateral hand (LH, RH and BH) finger movements. We found: (i) power, coherence and Granger causality spectra had significant peaks within the frequency band (0.01-0.04 Hz) during RS whereas the peaks shifted to a bit higher frequency range (0.04- 0.08 Hz) during btRS and finger movement tasks, (ii) there was significant bidirectional connectivity between all the nodes during RS and unidirectional connectivity from the LM1 to SMA and LM1 to LPMC during btRS, and (iii) the connections from SMA to LM1 and from LPMC to LM1 were significantly modulated in LH, RH and BH finger movements relative to btRS. The unidirectional connectivity from SMA to LM1 just before the actual task changed to the bidirectional connectivity during LH and BH finger movement. The unidirectionality could be associated with movement suppression and the bidirectionality with for preparation, sensorimotor update and controlled execution. These results underscore that fNIRS is an effective tool for monitoring spectral signatures of brain activity, which may serve as an important precursor before monitoring the recovery progress following brain injury.